THE PROCESS OF REFLECTION ON THE OWN PRACTICE, OF FUTURE PHYSICAL EDUCATION TEACHERS - Benites, Larissa Cerignoni (2019)
It is an experience report that had as objective to present the reflective process of five trainees of Physical Education teaching education, during their interventions in the Practicum in High School. For this purpose, four stages were used as the source of registration: (1) to describe what is done, (2) inform the meaning of actions, (3) confronting, questioning oneself and (4) rebuilding, thinking about how to do differently and was used a simple coding and categorization process. As a result, it is pointed out that throughout the records one can observe aspects of learning to analyze one's own practice, highlighting the effort in concretizing the expected actions of a teacher and the contrast with the apprehensions of future teachers. In this way, it was possible to perceive that there was a relationship between the stages of the reflexive process and the same ones were shown as a possibility to systematize what the pedagogical practice brings in the day-to-day exercise of teaching. Keywords: Practicum Courses. Physical Education. Reflection. Teacher Training.